"Cold turkey" or pharmacotherapy: Examination of tobacco cessation methods tried among smokers prior to developing head and neck cancer. Issue 7 (15th February 2019) - Khariwala, Samir S.; Rubin, Nathan; Stepanov, Irina; Nollen, Nicole; Ahluwalia, Jasjit S.; Nelson, Heather H.; Hatsukami, Dorothy K.
Abstract: Background: Tobacco cessation methods employed by patients with head and neck cancer (HNSCC) are previously unstudied and have the potential to inform choice of cessation method and necessary abstinence support. Methods: A total of 130 current smokers with HNSCC were queried regarding prior unsuccessful tobacco cessation techniques, product used (cold turkey, varenicline, and nicotine patch/gum), and maximum time abstained from smoking. Results: One hundred six smokers retrospectively reported using one of the four main quit methods. Unassisted cessation ("cold turkey") was the most commonly used method ( P < .001). A multiple ordinal logistic general estimating equation analysis revealed that cold turkey had increased odds [5.2 (95% confidence interval [CI]: 2.2, 11.8) and 4.3 (95% CI: 1.5, 12.9)] of achieving a longer quit duration than the nicotine patch or varenicline, respectively. Conclusions: Among smokers developing HNSCC, previous cessation attempts were most commonly unassisted. This method was associated with longest abstinence periods. These data suggest insufficient support and education regarding behavioral and pharmacologic cessation therapies.